Implementation of a fully variable valve actuation valvetrain - Jaffa, Steven (Department of Mechanical Engineering, 2015)
In January 2008 the Sasol (Pty) Ltd Advisory Board identified that the Sasol Advanced Fuels Laboratory's (SAFL) single cylinder research engine was not in line with the current engine technologies, in particular Fully Variable Valve Actuation (FVVA). This project represented the first stage of the engine upgrade, which was to modify the current single cylinder engine to interface with pneumatic valve actuators and a fully configurable Engine Control Unit (ECU).